Chirality of malaria parasites determines their motion patterns - Lettermann, Leon; Singer, Mirko; Steinbrück, Smilla; Ziebert, Falko; Kanatani, Sachie; Sinnis, Photini; Frischknecht, Friedrich; Schwarz, Ulrich S. (Nature physics, 2026)
Malaria parasites are injected by female mosquitoes into the skin of the vertebrate host and start to quickly move on helical trajectories, making them a medically highly relevant model system of active chiral particles. Here we find that these parasites always move on right-handed helices by analysing their three-dimensional motion in synthetic hydrogels. Furthermore, they transition to clockwise circular motion when they reach a two-dimensional substrate, which is the opposite direction to when circling on a two-dimensional substrate in a medium. This suggests that malaria parasites have evolved chirality as a means to control their transitions between three-dimensional and two-dimensional environments. Using a sandwich assay, we show that chirality also determines their transition from two-dimensional to three-dimensional motion. Combining a theory for gliding motility with two-sided traction force and super-resolution microscopies, we find that the most probable basis for the observed macroscopic chirality in both two and three dimensions is the asymmetric release of adhesion molecules at the apical polar ring. Our results suggest that the slender forms of the malaria parasites that start an infection have evolved very strong chirality because they have to switch between different physical environments.